Francis Bacon : a retrospective - Farr, Dennis, 1929-; Martino, Massimo; Bacon, Francis, 1909-; Peppiatt, Michael; Yard, Sally; Trust for Museum Exhibitions; Yale Center for British Art (New York : Harry N. Abrams in association with the Trust for Museum Exhibitions, 1999)
02